Is the femoral neck geometry adequate for placement of the proximal femoral nail in the Malaysian population? A review of 100 cases - Chiu, Chee Kidd; Chan, Chris Yin Wei; Singh, Vivek Ajit (Malaysian Medical Association, 2009)
Issues that had been encountered during proximal femoral fracture fixation using proximal femoral nail include i) the adequacy of the femoral neck width in the local population and ii) the potential difficulty encountered during fixation in certain prefixed angles as determined by the implant. This was a retrospective, descriptive study evaluating the anterior-posterior pelvic radiographs of 100 consecutive patients, from January to August 2007, managed at University Malaya Medical Centre, Kuala Lumpur. The femoral neck width in the population studied was adequate for placement of femoral neck screw and anti-rotation pin or hip pin using the proximal femoral nail implant. (mean = 34.0±3.7mm, min = 24.6mm). There was no significant difference between the working area using an implant angled at 130° or 135° (P=0.91). Both femoral neck width and neck shaft angle of the Malaysian population studied were not a factor influencing the placement of femoral neck lag screws and anti-rotation pin.